Mismatches in the coffee value chain: from basic needs to hedonistic lifestyles—experiences from Brazil, the Democratic Republic of Congo, and Switzerland. - Thom, B.; Sigrist, M.; Spath, L.; Banyanga, D.; Stettler, M.; Schneider, G.; Pfister, S.; Kintche, K.; Jacobi, J. (2025)
The coffee value chain (VC) faces several social-ecological challenges. Material resources and value creation are unequally distributed with a higher concentration at the end of the VC, mostly among multinational companies located in the global North. Companies and organizations of the global North dominate discourses and design and apply sustainability initiatives in origin countries, raising questions of legitimacy and impact. For sustainability initiatives to be successful, it may be necessary to involve different actors of the VC in decision-making processes and to better understand their views, needs, and priorities. In this study, we included different standpoints represented in ten case studies of different coffee VCs to explore what matters for different actors in Brazil, the Democratic Republic of Congo (DRC), and Switzerland. We adopted a mixed methods approach and conducted 1) focus group discussions with rural workers, metayers, (a type of sharecropper), farmers, and management/office staff of cooperatives and plantations in Brazil and DRC, 2) interviews with plantation owners and cooperative/company managers in Brazil and DRC, and 3) online surveys with roasters and consumers in Brazil, DRC, and Switzerland. We found a strong mismatch of the different perceptions of the different actors. Farmers strive for a dignified quality of life, plantation owners and cooperative/company managers for better economic conditions, rural workers for better working conditions, roasters for a great drinking experience, and consumers for pleasure and a hedonistic lifestyle. Our findings underline the importance of including diverse standpoints in coffee sustainability efforts, particularly those of rural workers and smallholders.